Does Working Capital Management Affect Profitability of Ghanaian Manufacturing Firms? - PREMPEH, Kwadwo Boateng; PEPRAH-AMANKONA, Godfred (Journal of Advanced Studies in Finance, 2019)
This paper analyses the relationship between working capital management and profitability of firms in the context of developing economies. A balanced panel of 11 manufacturing companies quoted on the Ghana Stock Exchange was used. The study covered the period 2011 to 2017. The relationship between working capital management and profitability was tested using dynamic panel regression (Arellano-Bond Estimation) technique. The study revealed that there is a significant positive linear relationship between working capital management and firms’ profitability. The findings also reveal the existence of a concave quadratic relationship between working capital management and firms’ profitability. Hence, an optimal level which maximises the profitability of manufacturing firms in Ghana exists. This implies that, there is an optimal level at which working capital management maximises firm’s profitability, therefore, managers need to ensure that they operate within the limits of the optimal level by implementing an effective and efficient working capital management policy. Also, the practice of an aggressive working capital management policy maximises a firm’s profitability.